COVID-19 in the elderly people and advances in vaccination approaches. Issue 12 (1st December 2020) - Dhama, Kuldeep; Patel, Shailesh Kumar; Natesan, Senthilkumar; Vora, Kranti Suresh; Iqbal Yatoo, Mohd; Tiwari, Ruchi; Saxena, Shailendra K; Singh, Karam Pal; Singh, Rajendra; Malik, Yashpal Singh
ABSTRACT: The rapid worldwide spread of the COVID-19 pandemic, caused by the newly emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has resulted in tens of millions of infections and over one million deaths. SARS-CoV-2 infection affects all age groups; however, those over 60 years old are affected more severely. Moreover, pre-existing co-morbidities result in higher COVID-19-associated mortality in the geriatric population. This article highlights the associated risk factors of SARS-CoV-2 infection in older people and progress in developing COVID-19 vaccines, especially for efficient vaccination of the older population. There is also a summary of immunomodulatory and immunotherapeutic approaches to ameliorate the outcome of COVID-19 in older individuals.